MEDICAL MANIPULATIONS ON EPILEPTIC PATIENTS - A. E. Kotov (Эпилепсия и пароксизмальные состояния)
Medical manipulations on epileptic patients are associated with risk of occurrence of seizures. However, such risk is often overestimated. In 902 epileptic patients examined, only 3 epileptic seizures were recorded, which have occurred during surgical intervention under general anesthesia. This article presents data on the effects of systemic anesthetics, surgical intervention itself and concomitant medicinal treatment over occurrence of epileptic seizures. The issues of epileptic patients’ preparation for elective surgery are discussed.